2016
DOI: 10.1158/1078-0432.ccr-15-2499
|View full text |Cite|
|
Sign up to set email alerts
|

Relationship between Tumor Biomarkers and Efficacy in EMILIA, a Phase III Study of Trastuzumab Emtansine in HER2-Positive Metastatic Breast Cancer

Abstract: Purpose HER2-positive breast cancer is heterogeneous. Some tumors express mutations, like activating PIK3CA mutations or reduced PTEN expression, that negatively correlate with response to HER2-targeted therapies. In this exploratory analysis, we investigated whether the efficacy of trastuzumab emtansine (T-DM1), an antibody–drug conjugate comprised of the cytotoxic agent DM1 linked to the HER2-targeted antibody trastuzumab, was correlated with the expression of specific biomarkers in the phase III EMILIA stud… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

10
158
3
1

Year Published

2016
2016
2022
2022

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 177 publications
(172 citation statements)
references
References 35 publications
(66 reference statements)
10
158
3
1
Order By: Relevance
“…Although alterations in some genes (e.g., EGFR, HER3, and PTEN protein expression and PIK3CA mutations; ref. 34) have been found to not correlate with T-DM1 response, data in this report warrant the investigation of caveolae-mediated endocytosis of T-DM1 in patient tumors as a potential predictive biomarker for response to T-DM1 and other non-cleavablelinked ADCs.…”
Section: Discussionmentioning
confidence: 65%
“…Although alterations in some genes (e.g., EGFR, HER3, and PTEN protein expression and PIK3CA mutations; ref. 34) have been found to not correlate with T-DM1 response, data in this report warrant the investigation of caveolae-mediated endocytosis of T-DM1 in patient tumors as a potential predictive biomarker for response to T-DM1 and other non-cleavablelinked ADCs.…”
Section: Discussionmentioning
confidence: 65%
“…More specifically, progression-free survival was 10.6 months for patients receiving therapy with tumors expressing higher Her2 levels versus 8.2 months for lower Her2 expression levels (8). Similarly, patients who received therapy harboring tumors with above median levels of Her2 had a median overall survival of 34.1 versus 26.5 months for patients with lower Her2 levels (8). These findings also have broad implications in formulating patient stratification strategies for a given ADC antigen target.…”
Section: Considerations For Target Selectionmentioning
confidence: 86%
“…As a case in point, the FDA approval of Kadcyla® for Her2-positive breast cancer was based on data from the phase III EMILIA trial; data from this trial suggested that patients with increased breast tumor expression levels of Her2 exhibited improved progression-free survival and overall survival. More specifically, progression-free survival was 10.6 months for patients receiving therapy with tumors expressing higher Her2 levels versus 8.2 months for lower Her2 expression levels (8). Similarly, patients who received therapy harboring tumors with above median levels of Her2 had a median overall survival of 34.1 versus 26.5 months for patients with lower Her2 levels (8).…”
Section: Considerations For Target Selectionmentioning
confidence: 97%
“…Based on the biomarker analyses from EMILIA and TH3RESA studies, T-DM1 was similarly effective in the presence of PI3K wild-type or mutated tumours, and the benefit with T-DM1 was seen irrespective of HER2 mRNA, HER3 mRNA, or PTEN protein level. 17,18 The current study is limited by its retrospective design, possible information bias during data retrieval/extraction/coding, as well as the small number of patients (especially for subgroup analysis) and inadequate follow-up period for OS. Although the results could not be compared directly with reported prospective trials, patients were representative, and treatment and outcomes reflect routine clinical practice.…”
Section: Discussionmentioning
confidence: 99%